Q fever is an old and neglected zoonotic disease in Kenya: a systematic review. (December 2016) - Njeru, J.; Henning, K.; Pletz, M.; Heller, R.; Neubauer, H.
Abstract Background Q fever is a neglected zoonosis caused by the bacteriumCoxiella burnetii . The knowledge of the epidemiology of Q fever in Kenya is limited with no attention to control and prevention programs. The purpose of this review is to understand the situation of Q fever in human and animal populations in Kenya in the past 60 years, and help identify future research priorities for the country. Methods Databases were searched for national and international scientific studies or reports on Q fever. We included studies and reports published between 1950 and 2015 if they reported on Q fever prevalence, incidence, and infection control programs in Kenya. Data were extracted with respect to studies on prevalence ofCoxiella infections, study design, study region, the study populations involved, and sorted according to the year of the study. Results We identified 15 studies and reports which qualified for data extraction. Human seroprevalence studies revealed evidence ofC. burnetii infections ranging from 3 to 35.8 % in all regions in which surveys were made and two Q fever outbreak episodes.Coxiella burnetii infections found in cattle 7.4–51.1 %, sheep 6.7–20 %, camels 20–46 %, and goats 20–46 % revealed variation based on ecoregions and the year of study. Farming and lack of protective clothing were associated with increased seropositivity among humans. However, high quality data is lacking on Q fever awareness, underlying cultural-economic factors influencingC. burnetii infection, and how the pathogen cycles may be embedded in livestock production and management systems in the economically and ecologically different Kenyan regions. We found no studies on national disease incidence estimates or disease surveillance and control efforts. Conclusion Coxiella burnetii infections are common in human and in a wide range of animal populations but are still unrecognized and underestimated thus presenting a significant human and animal health threat in Kenya. The factors influencing pathogen transmission, persistence and spread are poorly understood. Integrated disease surveillance and prevention/control programs are needed in Kenya.